BOTTLENECK POINT DALAM PENGEMBANGAN SARUNG TENUN DONGGALA - Shafira Algina; Asngadi Asngadi (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2022)
This study aims to identify and analyze bottleneck in developing Donggala weaving in Limboro Village of Donggala District. The type of research is descriptive qualitative. This research was conducted in Limboro Village, Donggala District, with a total of 4 informants. Data colledted by observation and indepth interview. The data analysis method used is the Nvivo 12 plus software. The results showthat a bottleneck in the developing of Donggala weaving occured in one of the production processes the name is ba hane work station.